Mechanism design of a small mobile robot for inspection of underground cables-in-pipe. (October 2020) - Zhou, Xuefeng; Zhao, Guowei; Zhao, Rui; Cheng, Yuan; Wang, Yishuang
Abstract: With the rapid growth of urban power load, underground cables-in-pipe is increasingly used in urban power transmission. The operation status inspection of underground cables-in-pipe is very important to guarantee the safety of power transmission. At present, mostly, the inspection of the underground cables-in-pipe is implemented by workers after cutting the power supply. Cutting power supply will cause economic loss. In addition, the workers cannot step into the narrow pipes, which lead to low inspection efficiency and the high omission factor. In order to solve the above problems, this paper proposes a novel mechanism of a small mobile robot for underground cables-in-pipe inspection. In the pipes where cables have been laid, the remaining space is narrow and irregular. Through the unique compact design of the robot mechanism, we make the robot able to run smoothly in the pipes. In this paper, we firstly establish the remaining space model of the cable-laid pipes. Then design the mechanism model of each part of the robot. After that, we determine the specific structural parameters. Finally, we carry out the feasibility analysis of the whole robot mechanism. The results of the analysis indicate that, the designed robot mechanism can move smoothly in underground cable pipes.